2002
DOI: 10.1002/jnr.10519
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae infection promotes the transmigration of monocytes through human brain endothelial cells

Abstract: We have investigated the effects of Chlamydia pneumoniae on human brain endothelial cells (HBMECs) and human monocytes as a mechanism for breaching the blood-brain barrier (BBB) in Alzheimer's disease (AD). HBMECs and peripheral blood monocytes may be key components in controlling the entry of C. pneumoniae into the human brain. Our results indicate that C. pneumoniae infects blood vessels and monocytes in AD brain tissues compared with normal brain tissue. C. pneumoniae infection stimulates transendothelial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 30 publications
1
73
0
Order By: Relevance
“…C. pneumoniae has been reported to stimulate transendothelial entry of monocytes through human brain endothelial cells 23 and all three Chlamydiaceae species multiply in monocytes. The findings of Wilke et al 28 of an increased number of monocytes in the blood of schizophrenic persons also support our assumptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. pneumoniae has been reported to stimulate transendothelial entry of monocytes through human brain endothelial cells 23 and all three Chlamydiaceae species multiply in monocytes. The findings of Wilke et al 28 of an increased number of monocytes in the blood of schizophrenic persons also support our assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…22 The importance of simultaneous infections with two C. species will be discussed later, particularly with regard to the blood-brain barrier. 23 Association of infections and HLA-A10 Elaboration of cytokines and specific neurotrophins during an immune response is controlled by the HLA system. We found recently an increased susceptibility to schizophrenia associated with HLA-A10 genotypes in two independent groups of patients.…”
Section: à3mentioning
confidence: 99%
“…Indeed, chronic inflammation from C. pneumoniae might be the trigger that activates the alternative complement pathway and ultimately leads to complement overactivity in patients with the Y402H risk variant of CFH, which as we have discussed above leads to impaired complement inhibitory function by CFH. Macrophage accumulation has also been associated with AMD, and prior studies have shown that C. pneumoniae infection promotes differentiation of monocytes to macrophages, as well as migration of monocytes to target tissues [93,94]. In fact, monocytes infected by C. pneumoniae upregulate various adhesion molecules and exhibit enhanced migration through the blood-brain barrier [94].…”
Section: Chlamydia Pneumoniae Infection and Amdmentioning
confidence: 99%
“…Macrophage accumulation has also been associated with AMD, and prior studies have shown that C. pneumoniae infection promotes differentiation of monocytes to macrophages, as well as migration of monocytes to target tissues [93,94]. In fact, monocytes infected by C. pneumoniae upregulate various adhesion molecules and exhibit enhanced migration through the blood-brain barrier [94]. This raises the question of whether Chlamydia can similarly enhance monocyte entry through the blood retinal barrier, as well as subsequent macrophage accumulation associated with AMD.…”
Section: Chlamydia Pneumoniae Infection and Amdmentioning
confidence: 99%
“…Vascular cell adhesion molecule-1 supports the adhesion of the primary leukocyte populations present in atherosclerotic plaques and may contribute to the quantitative predominance of monocytes over lymphocytes (Gerszten et al, 1998). Vascular cell adhesion molecule-1 facilitates transendothelial entry of circulating monocytes through human brain endothelial cells (MacIntyre et al, 2003), and it plays an important role in leukocyte recruitment in brain diseases, as shown in experimental models of systemic lupus erythematosus (James et al, 2003), and in chronic graft-versus-host disease (Sostak et al, 2004). At the bedside, soluble VCAM-1 concentration in plasma is raised in patients with acute stroke (Blann et al, 1999), and a two-fold increase of this parameter was found independently associated to poor outcome after stroke (Chamorro et al, 2002).…”
Section: Introductionmentioning
confidence: 99%